PENGEMBANGAN KAWASAN EKOWISATA KEBUN RAYA MANGROVE GUNUNG ANYAR DENGAN PENDEKATAN PENTAHELIX - Churin’in, Rachma Arsyieta; Soedarto, Teguh; Atasa, Dita (Jurnal Hutan Tropis, 2024)
Surabaya's Mangrove Botanical Garden, with an area of 25 hectares, offers views of the mangrove forest, jogging trails, a monitoring tower, boat docks and picnic areas. Despite its great tourism potential, visitor numbers are still relatively low and there are deficiencies in facilities and services. Data shows the destruction of mangrove ecosystems in Indonesia and the need for more attention to the management and promotion of this destination. Data shows that Indonesia's mangrove ecosystems, which cover 4.25 million hectares, are significantly damaged, with 48% moderately damaged and 23% severely damaged. Several Google Reviews cite deficiencies in infrastructure and management that affect visitor satisfaction. This study involved 25 respondents from pentahelix stakeholders (government, academia, business, community, media) and used qualitative descriptive analysis to identify ecotourism development patterns and strategies. This study aims to identify efforts to develop the Mangrove Botanical Garden ecotourism area through a pentahelix perspective, which involves the government, academics, business people, the community, and the media. Data analysis uses qualitative descriptive analysis. This analysis includes organising, simplifying and synthesising data to identify patterns and main themes, as well as formulating working hypotheses. Overall, the Gunung Anyar Surabaya Mangrove Botanical Garden shows positive developments in environmental conservation efforts and ecotourism development. The botanical garden manager has planned various strategic steps to improve the attractiveness and quality of services, which are expected to have a positive impact on both visitors and the surrounding environment.